Four rare earth elements that will only get more important - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Chin, Mei Lee; Siti Aisah, Harun; Norhayati, Nordin; Ezrinda, Mohd Zahidee; Mohd Fazli, Farida Asras; Nurul Nadia, Abd Razak (Penerbit UMP, 2011)
Rare earth elements are neither rare, nor earth and they tend to be things that are added, in small doses, to composites and alloys. Rare earths have really unique chemical and physical properties-that allow them to interact with other elements and get results that neither element could get on its own. Rare earth elements are crucial to the way we live now; responsible for miniaturizing computers and headphones, powering hybrid cars and more. Rare earth elements-a set of 17 related metals, mostly shunted off to a tacked - on lower line of the periodic table- are crucial to the way we live now; responsible for miniaturizfn9 computers and headphones, powering hybrid cars and more. The time has come to get better acquainted with the molecules that make our modern world run.